2013
DOI: 10.2478/pjvs-2013-0048
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and immunohistochemical characteristics of the pterygopalatine ganglion in the chinchilla (Chinchilla laniger, Molina)

Abstract: Histological and histochemical investigations revealed that the pterygopalatine ganglion (PPG) in the chinchilla is a structure closely connected with the maxillary nerve. Macro-morphological observations disclosed two different forms of the ganglion: an elongated stripe representing single agglomeration of nerve cells, and a ganglionated plexus comprising smaller aggregations of neurocytes connected with nerve fibres. Immunohistochemistry revealed that nearly 80% of neuronal cell bodies in PPG stained for ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 34 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Galanin presence was demonstrated in the plexuses of the stomach muscular layer of pig and wild boar [27] and in the PPG of pig, chinchilla and cat [37][38][39]. GAL-IR has been observed in chinchilla in a few perikarya (2-3 per section) and in individual intraganglionic nerve fibers of the PPG [38].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Galanin presence was demonstrated in the plexuses of the stomach muscular layer of pig and wild boar [27] and in the PPG of pig, chinchilla and cat [37][38][39]. GAL-IR has been observed in chinchilla in a few perikarya (2-3 per section) and in individual intraganglionic nerve fibers of the PPG [38].…”
Section: Discussionmentioning
confidence: 89%
“…GAL-IR has been observed in chinchilla in a few perikarya (2-3 per section) and in individual intraganglionic nerve fibers of the PPG [38]. In pig PPG a small number (approximately 6%) of GAL-IR neurons and single nerve fibers was found with all GAL-positive neurons containing also VIP [37].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, we failed to visualize somatostatin-IR neuronal elements in the porcine PPG. Previously, it has been reported that a relatively small subpopulation of somatostatin-IR small-sized neurons exists in the porcine [11] and chinchilla's PPG [7]. …”
Section: Discussionmentioning
confidence: 99%
“…From the morphological point of view, at least two different forms of PPG can be distinguished. Precise macroanatomical studies revealed that PPG may exist as either a large aggregation of nerve cells grouped in a single ganglion or a small plexus containing several smaller in size ganglia [7]. Previous studies have also shown that PPG parasympathetic neurons are predominantly cholinergic by nature, however the presence of other neurotransmitter markers including tyrosine hydroxylase or nitric oxide synthase has been additionally noted [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation